2019
DOI: 10.1186/s13148-019-0785-z
|View full text |Cite|
|
Sign up to set email alerts
|

ZMYND10, an epigenetically regulated tumor suppressor, exerts tumor-suppressive functions via miR145-5p/NEDD9 axis in breast cancer

Abstract: BackgroundRecent studies suggested that ZMYND10 is a potential tumor suppressor gene in multiple tumor types. However, the mechanism by which ZMYND10 inhibits breast cancer remains unclear. Here, we investigated the role and mechanism of ZMYND10 in breast cancer inhibition.ResultsZMYND10 was dramatically reduced in multiple breast cancer cell lines and tissues, which was associated with promoter hypermethylation. Ectopic expression of ZMYND10 in silenced breast cancer cells induced cell apoptosis while suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…TSGs are critical in the mediation of tumorigenesis 3 , 4 . Thus, identifying new TSGs and addressing unknown molecular events in BrCa is essential to characterizing carcinogenesis mechanisms, establishing novel prognostic biomarkers and even developing efficient therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSGs are critical in the mediation of tumorigenesis 3 , 4 . Thus, identifying new TSGs and addressing unknown molecular events in BrCa is essential to characterizing carcinogenesis mechanisms, establishing novel prognostic biomarkers and even developing efficient therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor suppression genes (TSGs) are critical for tumor progression, which are often downregulated and frequently silenced by DNA methylation in BrCa 3 , 4 . DNA methylation is the major epigenetic modification 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To determinate the mechanism underlying the effects of miR-25-5p in OSCC cells, the candidate target genes of miR-25-5p were predicted using the TargetScanHuman7.2 ( ) and miRWalk ( ). Among these target genes of miR-25-5p, KLK9, WNT3A, FGF18, SRSF4, FIBP, SOX12, TGFBI, and NEDD9 have been reported to participate in the development human cancers ( 42 49 ). Thus, we selected these genes for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…There are lots of target genes of miR-25-5p according to the results of quick search on TargetScan databases. Among these target genes, KLK9, WNT3A, FGF18, FIBP, SOX12, TGFBI, and NEDD9 have been reported to participate in the development of human cancers ( 42 49 ). The results of RT-qPCR indicated that among KLK9, WNT3A, FGF18, SRSF4, FIBP, SOX12, TGFBI, and NEDD9, the expression of NEDD9 was much higher in OSCC tissues than adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation